Heart or Grace Score for Diagnostic and Risk Stratification in Acute Coronary Syndrome Patients - Friendina Napitupulu; Harris Hasan; Abdullah Afif Siregar (Talenta Publisher, 2025)
Background: Some studies found that HEART score is better than GRACE score either as a rule-in method for myocardial infarction or as a risk stratification. However, GRACE score was also found to have better discriminatory ability as a prognostic model for patients with myocardial infarction. Objective: This study aims to evaluate whether the HEART and GRACE scores have equal capabilities either as a diagnostic method for myocardial infarction or risk stratification to predict in-hospital Major Adverse Cardiovascular Events (MACE) in Acute Coronary Syndrome (ACS) patients at Adam Malik Hospital. Methods: This research is a retrospective and prospective observational study. Retrospective data was collected from all medical records of ACS patients from January to December 2022. Prospective data was collected by consecutive sampling until 46 samples were fulfilled from October 2023 at Adam Malik Hospital. Samples included in the research analysis were those who met the inclusion criteria. To compare each score, we use the area under the receiver-operating characteristics (AUC) method. Results: HEART score is superior to GRACE score as a diagnostic method with an AUC of 0.903, a cutoff of 6.5, sensitivity of 86%, and specificity of 80%. The GRACE score is superior to the HEART score as a risk stratification with an AUC of 0.719, a cutoff of 128.5, sensitivity of 66%, and specificity of 65%. Conclusion: HEART score is superior for diagnosis, and GRACE score is superior for risk stratification.